Identify the factors pushing and pulling interest in revisiting millennial tourists to the Kintamani tourist area, Bali - Darsana, I Made; Kartimin, I Wayan; Sudarmawan, I Wayan Eka (Jurnal Mantik, 2024)
One of the determining factors in the success of a tourism destination is the emergence of tourists' interest in visiting again, because it can have a significant impact on the local economy and tourism industry. In recent years, a new trend has emerged in the world of traveling where the majority of people traveling are young people, known as the millennial generation. This study aims to analyze the push factors and pull factors for millennial generation tourists in making repeated tourist visits to the Kintamani Tourism Area in Bali. The method used in this research is an exploratory descriptive method. The variables used are tourist characteristics and motivation to visit which are divided into two sub-variables, namely push factors and pull factors. Data was obtained through a survey by distributing questionnaires using purposive sampling to 80 millennial tourists who visited the Kintamani Tourism Area. Next, data analysis was carried out using descriptive statistics in the form of tables and graphs to draw conclusions. The research conclusion is that there are 4 push factors (escape/looking for entertainment, relaxation, romance, educational opportunity) and 2 pull factors (natural beauty and climatic conditions) that determine the interest of millennial tourists in returning to the Kintamani Tourism Area